F-box proteins in cancer stemness: An emerging prognostic and therapeutic target - Abdul Q. Khan (14153247) (2021)
Cancer is a complex heterogenic disease with significant therapeutic challenges. The presence of cancer stem cells (CSCs) in cancer tissue orchestrates tumor growth, progression, and metastasis, the tumor heterogeneity, disease relapse, and therapeutic resistance. Hence, it is imperative to explore how progenitor or cancer-initiating cells acquire stemness features and reprogram different biological mechanisms to maintain their sustained oncogenicity. Interestingly, deregulation of F-box proteins (FBPs) is crucial for cancer stemness features, including drug resistance and disease relapse. In this review, we highlight recent updates on the clinical significance of targeting FBPs in cancer therapy, with emphasis on eliminating CSCs and associated therapeutic challenges. Moreover, we also discuss novel strategies for the selective elimination of CSCs by targeting FBPs. Other Information Published in: Drug Discovery Today License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.drudis.2021.07.006